2017
DOI: 10.1021/acs.jctc.7b00224
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transformations Approaching Chemical Accuracy via Correlated Sampling in Auxiliary-Field Quantum Monte Carlo

Abstract: The exact and phaseless variants of Auxiliary-Field Quantum Monte Carlo (AFQMC) have been shown to be capable of producing accurate ground-state energies for a wide variety of systems including those which exhibit substantial electron correlation effects. The computational cost of performing these calculations has to date been relatively high, impeding many important applications of these approaches. Here we present a correlated sampling methodology for AFQMC which relies on error cancellation to dramatically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 121 publications
2
79
0
Order By: Relevance
“…For the isolated ligands, we confirmed the convergence of the energy from ph-AFQMC/PC calculations with increasingly large active space sizes, and found that in all cases except for the sulfur and fluorine atoms, CASSCF did not lower the energy by more than a milli-Hartree with respect to unrestricted Hartree Fock (UHF). Hence, we use UHF for these cases, CASSCF(6e,8o) for S, and CASSCF(7e,16o) for F. The latter is consistent with our previous work, 46 in which we found that an active space of this size was necessary to obtain chemically accurate electron affinities for the F atom.…”
Section: Computational Detailssupporting
confidence: 81%
See 3 more Smart Citations
“…For the isolated ligands, we confirmed the convergence of the energy from ph-AFQMC/PC calculations with increasingly large active space sizes, and found that in all cases except for the sulfur and fluorine atoms, CASSCF did not lower the energy by more than a milli-Hartree with respect to unrestricted Hartree Fock (UHF). Hence, we use UHF for these cases, CASSCF(6e,8o) for S, and CASSCF(7e,16o) for F. The latter is consistent with our previous work, 46 in which we found that an active space of this size was necessary to obtain chemically accurate electron affinities for the F atom.…”
Section: Computational Detailssupporting
confidence: 81%
“…Recently we have introduced a correlated sampling (CS) approach for quantities involving energy differences which is capable of reducing computational prefactors 46 and in some cases the severity of the phaseless approximation. 43 In this section, we show that significant reductions in statistical errors are obtained not only for hydrogen abstraction reactions, as shown previously, but also for bond breaking events between a transition metal and a heavier ligand atom.…”
Section: Correlated Sampling For Bdesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the cost of achieving the same statistical error for larger systems adds an extra O(N ) to the computational cost of ph-AFQMC. This extra cost for sampling may be avoided by the correlated sampling technique 119,120 , but here we instead compare the total energy per electron. This metric is well-suited for ab-initio solids (or extended systems) in general.…”
Section: Larger Supercellsmentioning
confidence: 99%